Takdir dalam Islam (Suatu Kajian Tematik) - Iril Admizal (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2021)
Qadha is a problem that has been discussed since the time of the Prophet, friend, Tabi'in and until now. The issue of fate is very interesting to discuss, because there are several sects that view qadha differently. The first group says that qadha is a decree of Allah which cannot be contested, including human actions, there is already a provision of Allah. The second group argues that qadha is not the absolute will of Allah. However, Allah gave power to humans and humans were given the freedom to control it. So what determines human qadha is himself depending on how a person uses the power given by Allah. And the third Group takes the opinion that qadha can be in the form of God's absolute decree and it can also be in the form of power given to humans and humans themselves who direct that power. To better understand the problem of qadha more deeply, the writer understands the verses in the al-quran and sees the opinions of the tafsir scholars then packs them in the form of a thematic method, so that they can meet a problem solving point. From the results of the research that the author did, there were 133 qadha words in the al-Qur'an with various finished words. Then the authors see from the language dictionary it turns out that the meaning of the word qadha means measuring, grading or measuring so that we can understand that qadha is the limit, size, content and provisions that Allah has given to humans. So it can be concluded that qadha is not an absolute provision of Allah, but qadha that occurs in humans has a law of causality or cause and effect, and in the law of cause and effect also applies God's inayah (help).